Knowledge of the Pragmatici Legal and Moral Theological Literature and the Formation of Early Modern Ibero-America - Duve, Thomas; Danwerth, Otto (Max-Planck Studies in Global Legal History of the Iberian Worlds, 2020)
Knowledge of the pragmatici analyses pragmatic normative literature in colonial Ibero-America. It explores the circulation and the functions of these media in the Iberian peninsula, New Spain, Peru, New Granada and Brazil. Readership: All interested in the legal history, the history of knowledge and book history in early modern times, especially with regard to colonial Ibero-America.